An Unusual Case of Gullo’s Syndrome Concomitant with Serious Endometriosis Disease in a Postmenopausal Woman - Abdelhakim Ainahi; Abdellaziz Ziane; Lahcen Wakrim; Naima Elmdaghri; Abdelhamid Barakat (Case Reports in Medicine)
Gullo’s syndrome is a singular physiological phenomenon defined by an abnormal increase in serum pancreatic enzyme levels that may occur in healthy subjects in the absence of pancreatic disorders. During routine health examination in a 54-year-old postmenopausal woman with severe endometriosis, elevated values of serum amylase and lipase were fortuitously observed (198 and 1461 U/L, resp.). Over five years of regular pancreas surveillance, all clinical, biological, and imaging investigations were normal. However, the pancreatic enzyme levels have shown considerable fluctuations including some episodic transient normalization. The description of this benign pancreatic hyperenzymemia case incidentally associated with endometriosis disease is a very rare clinical situation. More in-depth documentation of this phenomenon may help clinicians to avoid unnecessary diagnostic management approaches and reassure the concerned patients that this affection would not be so worrying.